Outcomes of Health Service System Development on Quality of Life of People in Pattani Province - ลำโป ชัยรัตน์; วังทอง อังคณา; วังทอง อนุชิต (Journal of Health Science of Thailand, 2022)
The objective of this study was to assess the outcomes of health service system development on quality of life of people in Pattani Province. It was conducted using research and development approach with 8-year study period using quality of life measurement through participatory group discussions. Three phases of study were carried out. The phase 1 (pre-development phase) was to assess preliminary data on quality of life of people of which the 2 areas were analyzed: (1) health service system and (2) health care outcomes; and the baseline levels were obtained. Phase 2: the development phase of the health service system in accordance with the concept of a small house in a big forest and a participatory research model. It was divided into 2 steps as follows: (1) assessing people’s quality of life which revealed that the study samples had a good overall quality of life, and (2) the development of the quality of life measurement tool according to the age group that covered 4 components, namely physical health, mental health, social relationship and environment. The phase (3): the post-development phase, which was divided into 2 steps: (1) the study of people’s quality of life by age group. Based on the results, all age groups had better levels of overall quality of life which varied significantly among the different age groups (p<0.05), and (2) the study of people’s perceptions on quality of life improvement which found that the people’s perceptions was at a high level both the overall perception and the 4 study components. It was recommended that the health service system should be integrated with holistic participation in order to become more effective, particularly at the community level.